IPTEKS BAGI WILAYAH (IBW) DI KECAMATAN KLOJEN KOTA MALANG - Mukarom, Mukarom; Sucipto, Adi; Afrida, Indah Rakhmawati; Andriyono, Djoko; Rusdi, Rusdi; Sufiyanto, Sufiyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2017)
Development in the city of Malang is directed to bring the people of Malang City to the welfare that is distributed evenly. This condition is characterized by increasing economic growth, declining unemployment and decreasing the poor in Malang. In addition, it will also lead people to increasingly cultured conditions, with religious-tolerant values marked by an increasing understanding of traditional values, religious values, mutual respect for differences, and the absence of conflict and violence on behalf of SARA in the city of Malang. The objectives of IbW Program are: (1) To identify potential, actual condition / situation, human resources and realistic resources in Klojen Sub-district, Malang City; (2) To formulate the potential of human resources and natural resources so that it can be used as a pre-eminent commodity of the region; (3) Conducting training activities in the framework of technology transfer generated by Higher Education to the community, so that the community has the knowledge and skills in managing the potential around them. Activities were carried out using survey methods, and observations. Meanwhile, to arrange the action program is done through worshop activity with the hope of action program as needed by society. To that end, in this IbW activity the community is involved from program planning, program implementation, utilization of results and evaluation of program implementation. In this way, the action program is a program that fits the needs of the community. In addition, the implementation of community empowerment activities is carried out using field assistance method. The results of IbW program activities that have been implemented are: (1) Health Sector; Drug hazard counseling; (2) Education Sector; Improved quality of educators with Class Action Research (PTK) training; Mentoring learning for underprivileged students; (3) Economic Program; Entrepreneurship Training